Stereographic Photography on the Computer - Blade, Richard A. (International Journal of Virtual Reality, 1995)
The author provides a semi-technical review of the principles of stereographic photography usable without special equipment and discusses the current methods of viewing stereo photographs as computer images. Included is a discussion of recently developed commercial software called Wireframe Express that allows two or more photographic images of an object, taken at different but arbitrary positions, to be joined into a composite 3D model for stereographic viewing from any angle. Among other things, this recent technology allows the virtual reality simulation of historic buildings and rooms to be constructed from currently existing photographs. Illustrations of the points are made with images provided on the CD-ROM.